Design of a Monitoring Tool for Eco-Regions - Cesare Zanasi; Salvatore Basile; Flavio Paoletti; Patrizia Pugliese; Cosimo Rota (Frontiers in Sustainable Food Systems, 2020)
An Eco-Region (Biodistretto in Italian) is a rural area where different actors work together for the sustainable management of local resources, based on the principles and models of organic farming. Social, environmental, economic as well as ethical dimensions are involved. Eco-Regions are quickly growing in number in the EU and worldwide; different Eco-Regions types emerged, showing a variety of cultural, physical, socio-economic characteristics, and related policies and regulations. The Eco-Regions represent an innovative sustainable integrated rural development approach; their success can be supported by analyzing their basic features and their development dynamics. A balance between a strictly centralized and bureaucratic Eco-Regions management and a bottom-up non-regulated Eco-Regions proliferation should be provided to grant the development of community-based resilient initiatives. To this end a monitoring tool, based on the Porter's Diamond model, involving the local actors in analyzing the Eco-Regions structure and performances, could provide useful. Previous studies defined an Eco-Region monitoring tool, where different shortcomings characterized the analytical framework definition. The goal of the present paper is therefore to define an improved monitoring tool, more consistent to the Porter's Diamond model by reviewing the cluster related literature, focusing on the Porter's approach. The integrations resulting from the literature analysis contributed to a major increase in the indicators directly related to the original Porter's approach; new food security and sovereignty, as well as specifically designed sustainability indicators have also been added. By expanding the pool of indicators, the monitoring tool is more adaptive and able to support sustainable management of Eco-Regions in different contexts.